Teaching Strategies in Qur’anic Education for Deaf and Hard-of-Hearing Students: A Systematic Literature Review - Hermon Susanto; Elsa Efrina; Antoni Tsaputra; Zadrian Ardi; Hermon Susanto; Elsa Efrina; Antoni Tsaputra (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Qur'anic education for deaf and hard-of-hearing (DHH) students is a critical dimension of inclusive Islamic education yet remains underserved due to the predominantly auditory nature of traditional instruction. This study systematically analyzes instructional strategies, pedagogical methods, effectiveness outcomes, implementation challenges, and future recommendations for Qur'anic learning among DHH students. A Systematic Literature Review (SLR) combined with bibliometric analysis was employed as the methodological framework. Data were retrieved from the Scopus database and screened in accordance with PRISMA guidelines, yielding five empirical articles that satisfied the predefined inclusion criteria. Analysis proceeded through bibliometric mapping and thematic synthesis. Findings reveal that Hijaiyah sign language and staged instructional approaches constitute the predominant strategies, with visual and multisensory methods demonstrating significant effectiveness in improving Qur'anic literacy encompassing reading, tajwid comprehension, and memorization. However, instructional effectiveness is conditioned by teacher competence, availability of appropriate learning media, and environmental support. Bibliometric analysis further indicates that technological integration remains nascent, representing a substantive gap and opportunity for future inquiry. This study contributes a structured scientific synthesis to the field of inclusive Islamic education and underscores the need for technology-driven pedagogical innovations, adaptive curricula, and systematic teacher preparation programs.